GETTING ANTIOXIDANTS AND OTHER BENEFITS FROM WILD BLUEBERRIES - Tukhtaboev , Mokhirjon Rakhimjanovich (Educational Research in Universal Sciences, 2024)
Blueberries are used as food and for making liqueurs, jelly, jam, and pies. Also stored frozen. In many places, berry picking brings significant income to the population. Blueberries are low in fruit acids. But they are high in A and B vitamins, manganese, fiber and flavonoids. Berries are a good source of vitamin C, magnesium and calcium. A good honey plant, produces a lot of nectar. Fragrant honey is light, slightly reddish. The nectar productivity of one flower in the conditions of the widespread in north Euro Asia and North America in shady places is 0.3 mg, in semi-shaded places 0.4-0.5 mg. The coloring matter of blueberries is a (pH) indicator and changes color to blue when the acidity decreases.